2009
DOI: 10.1007/s10557-009-6181-8
|View full text |Cite
|
Sign up to set email alerts
|

Increased Levels of 25 Hydroxyvitamin D and 1,25-Dihydroxyvitamin D After Rosuvastatin Treatment: A Novel Pleiotropic Effect of Statins?

Abstract: This study has shown an effect of rosuvastatin on vitamin D metabolism, with an increase in both 25-hydroxyvitamin D and 1,25-dihydroxyvitamin D. This may be an important pleiotropic effect whereby rosuvastatin reduces mortality in patients with coronary artery disease. Further studies are needed to clarify the relationship between statins and vitamin D metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
81
2
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(85 citation statements)
references
References 19 publications
1
81
2
1
Order By: Relevance
“…Previous studies reported different results about the association between statin use and serum 25(OH)D. Rosuvastatin (6,8) and atorvastatin (7) were found to increase serum levels, whereas fluvastatin and simvastatin did not change these levels significantly (6,37). We observed no significant association between statin use and serum 25(OH)D. In the first cohort we performed the same analysis, despite the user group being less than 5% of the population.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Previous studies reported different results about the association between statin use and serum 25(OH)D. Rosuvastatin (6,8) and atorvastatin (7) were found to increase serum levels, whereas fluvastatin and simvastatin did not change these levels significantly (6,37). We observed no significant association between statin use and serum 25(OH)D. In the first cohort we performed the same analysis, despite the user group being less than 5% of the population.…”
Section: Discussionmentioning
confidence: 64%
“…To our knowledge, information about the influence of medicines on serum 25(OH)D is limited. For example, some statins (6,7,8) are found to elevate serum 25(OH)D, whereas anti-epileptic drugs lower serum 25(OH)D (9,10). Further knowledge about associations is warranted, because of the large influence of vitamin D in several physiological processes (1) and the possibility to prescribe vitamin D supplements in case of a lowering effect.…”
Section: Introductionmentioning
confidence: 99%
“…26 Vitamin D deficiency, defined as levels of 25(OH)D <30 ng/mL, were found in 37 of 64 (58%) of our patients. Thus, the test of vitamin D status was more often abnormal than normal and therefore clinically important on its own merits since 31,32 although not in all studies, 33 and this may contribute in a small way to the cardioprotective effects of statin therapy. 34 In a small drug interaction study, vitamin D supplementation lowered LDL cholesterol despite lowering blood levels of the statin.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the striking benefit achieved with statin treatment in patients with a wide range of cholesterol concentrations cannot be attributed to their cholesterol-lowering effect alone, but rather to additional pleiotropic effects. One of these pleiotropic effects may be mediated in part by an effect on 25OHD metabolism (14 ), and there is some evidence that statins can improve 25OHD concentrations in patients with familial hypercholesterolemia and ischemic heart disease (15)(16)(17)(18).…”
Section: Methodsmentioning
confidence: 99%